The Effect of Fusarium Fungal Inoculation, Hole Position, and Induction Technique on Forming Agarwood in Gyrinops versteegii Tree - Rawana, Rawana; Hardiwinoto, Suryo; Budiadi, Budiadi; Rahayu, Sri; Prijono, Agus (Institut Pertanian Bogor (IPB University), 2024)
Gyrinops versteegii, belonging to the Themelaeaceae family, is one of the species producing high-grade agarwood. The induction technique can accelerate the agarwood product. This study inducted the G.versteegii tree with fungal species, a variation of hole position, and an induction technique. The research was done at a domesticated G. versteegii plantation in Sragen and Karanganyar District, Central Java Province. The agarwood quality resulted from the inoculated G.versteegii tree characterized by the wood aroma, the discolouration area, wood aroma, and terpenoid content, is significantly affected by the wood position in the stem, the fungal species, and the inoculation technique. The upper stem results the better agarwood than the bottom stem. Using the inoculant of the Fusarium oxysporum can achieve better agarwood than the inoculant of F.solani and mixed F.solani x F.oxysporum. Furthermore, the infusion technique gains a better agarwood result than others. Keywords: domesticated G.versteegii, wood aroma, discolouration, and terpenoids.